Role of Social Media in Medical Education - Agrawaal, Krishna Kumar; Agrawal, Ankita (Journal of Universal College of Medical Sciences, 2023)
Social Media has become a revolution. More than half of the world’s population use social media. Covid 19 pandemic increased the use of social media for medical education. Different online platforms using Web 2.0 technology has come up with innova- tive ideas for medical education. An enhanced online presence has the potential to make positive contributions to professional development, education and collaborations, potentially opening doors to academic opportunities. Journal clubs have evolved from traditional classroom based to online platforms such as twitter. Tutorials have become tweetorials. Academic achieve- ments from impact factor-based publication have now become alternative metrics score (Altmetrics). Here, in this article we discuss different aspect of social media to enhance education, research and clinical practice in modern medicine.